PEMBERIAN IDENTITAS PENDUDUK PEKERJA SEKTOR INFORMAL DI JAKARTA MENURUT UNDANG – UNDANG NOMOR 23 TAHUN 2006 - Kholiah Qurtubi, Untung Sri Hardjanto, Retno Saraswati (Diponegoro Law Journal, 2012)
Administration of population in Indonesia is a very important rule in development. Act No.23 of 2006 has set the administration that in it enforces the use of the Population Administration Information System (SIAK) which aims to provide information to support the administration that is in line with advances in information and communications technology to meet the demands of the public for the service professional  population. The number of migrants working in the informal sector who do not know how to get an ID and they did not take care of migrate letter which  resulted  in  increased  population  growth  in  Jakarta.  Thus,  the  SIAK  can  assist  the Government in the record will be more efficient and effective. The method used is the normative juridical approach used to determine the legal norms contained in the legislation. Specifications research  in legal writing is descriptive analysis, the study describes the legislation in force associated with the theories of law and positive law concerning the implementation of the above- mentioned problems. The  result  of  the  study  is  the  presence  SIAK  governing  the  manufacture  of  residence identification card,  family card, and other population letter will be more effective than the manufacture of identity cards that do not use SIAK. This is because the manufacturing process is cheaper and faster.